How to cope with Long COVID – A qualitative interview study on stressors and coping strategies of people affected by long-term consequences of COVID-19 - Melanie Elgner; Marius Binneböse; Josi Großmann; Tamara Frank; Paul Bruckmann; Claas Lahmann; Katrin Elisabeth Giel; Christine Allwang; Florian Junne; Hannah Wallis (PLoS ONE, 2026)
Long COVID, a multi-system-disease characterized by persistent somatic and mental symptoms following a SARS-CoV-2 infection, can severely impair health and quality of life of those affected. In the absence of adequate therapeutic approaches and a fragmented care landscape, our focus is on identifying individual stressors, the resulting needs and strategies people use to cope with the ongoing burden of the disease and its long-term stressors. This qualitative interview study is part of a pilot multicenter study addressing psychosocial needs in patients with Long COVID. The surveyed sample (n = 40) consists of affected people, who suffer from persistent symptoms and psychosocial stress after a SARS-CoV-2 infection. Based on the Transactional Stress Model according to Lazarus and Folkman and the Brief COPE by Carver, the qualitative analysis of semi-structured interviews focused on the various and individual coping attempts of the interviewees. Participants reported a wide range of persistent physical and mental complaints. Fatigue-associated complaints, cognitive impairments, fears and worries were mentioned frequently and perceived as particularly stressful. Job insecurity and financial worries, lack of recognition, stigmatization, lack of treatment and therapy approaches, withdrawal and social isolation were reported as stressors. In most cases, we identified an interplay between emotion-oriented (such as emotional support, self-care and positive thinking) and problem-oriented coping strategies (such as planning/pacing, self-help, withdrawal and avoidance). Emotional support as the most frequently mentioned strategy and as a fundamental resource in coping with this disease should be strengthened. These findings offer a valuable insight into the diverse stressors and coping patterns in dealing with post-viral symptoms of COVID-19. The analysis reveals that complaints and attempts to cope vary significantly among the participants. This underlines the importance of providing tailored support to those affected to help them manage their symptoms, improve their quality of life and enable them to participate in social life again.